2021
DOI: 10.1364/oe.413942
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of deep sub-wavelength nanowells by imaging the photon state scattering spectra

Abstract: Optical-matter interactions and photon scattering in a sub-wavelength space are of great interest in many applications, such as nanopore-based gene sequencing and molecule characterization. Previous studies show that spatial distribution features of the scattering photon states are highly sensitive to the dielectric and structural properties of the nanopore array and matter contained on or within them, as a result of the complex optical-matter interaction in a confined system. In this paper, we report a method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…PIMI is a polarization imaging technique for visualization of end-face in semiconductor light-emitting chips, which can reflect the photon state distribution of the polarization-modulated light beam after its interaction with end-face structure [13,15]. Since different material layers Comparisons of intensity profiles between TM and sin δ images, here sin δ is easy to observe complete SLD spots as well as asymmetries, especially its spot boundaries.…”
Section: Optical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…PIMI is a polarization imaging technique for visualization of end-face in semiconductor light-emitting chips, which can reflect the photon state distribution of the polarization-modulated light beam after its interaction with end-face structure [13,15]. Since different material layers Comparisons of intensity profiles between TM and sin δ images, here sin δ is easy to observe complete SLD spots as well as asymmetries, especially its spot boundaries.…”
Section: Optical Modelsmentioning
confidence: 99%
“…Such multi-dimensional images provide additional insight to resolve the geometrical features of the measured nanostructures, enabling PIMI an outstanding and non-invasive tool for label-free optical imaging with high resolution and simple setup [13]. So far, this method has been successfully employed to analyze the structural characteristics such as dimensions and shapes of graphene layers, nanoparticles, and other dielectric or metallic samples [10,[13][14][15][16][17], providing a solid basis for us to improve the detection ability to the end face in the semiconductor light-emitting devices. Due to the diverse reflection and scattering characteristics of the different material layers and the possible impurities in the end face, when a beam of polarized light strikes the end face, multilayers will interact with the incident photons states and generate different responses, and then structural features will be encoded to the scattering signals.…”
Section: Introductionmentioning
confidence: 99%
“…PIMI provides a series of parametric images which reflects the detailed nanoscale properties of the sample which is unable to be uncovered in conventional microscopes. Therefore, it has been effectively applied for investigating the morphological and structural features of graphene layers [1], nano-particles [2] and nanopores [11]. PIMI system has been proved to be able to obtain information about nanostructures, making it possible to screen for the early infection by detection of viral particles with an optical system.…”
Section: Signal Denoising and Viral Particle Identification In Wide-f...mentioning
confidence: 99%
“…PIMI obtains anisotropic nanoscale structural information about the sample by utilizing a polarization modulated illumination scheme and analyzing the far-field variation of polarization states of the scattered photons. By fitting and filtering the intensity variations of the image pixels, a set of parametric images, such as sin(δ) and Φ images, can be obtained in which the spatial resolution is greatly enhanced compared to conventional optical microscopy, enabling the collection of features smaller than 100 nm [18]. As shown in Fig.…”
Section: Pimi Data and Pre-processingmentioning
confidence: 99%
“…In our previous work, we have investigated the ability of polarization indirect microscopic imaging (PIMI) to resolve nano-features and molecular structures from the spatial polarization status distribution in the nano scattering field [15][16][17][18]. We also demonstrated that anisotropy in nanostructures can be identified from the scattered photon distribution [19,20].…”
Section: Introductionmentioning
confidence: 99%